Social Capital Management Members of The Hijrah Community Jaga Sesama Solo - Desy Wulandari; Nurhadi Nurhadi; Danang Purwanto (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2022)
The aim of this research is to explain about the management of social capital by the members of “Pemuda Hijrah Jaga Sesama”. The data has been collected by interview and documentation. The informants were choose by the snowball sampling method. The five informants are the administration and the members of “Pemuda Hijrah Jaga Sesama”. The writer choose “Pemuda Hijrah Jaga Sesama” as the subject of the research is because they have a large congregation in the city of Solo and has a structured routine agenda. The data analysis is done by domain analysis and the social capital theory, and continued with the triangulation source and method as the data validation. The results of this research find out that members of the Jaga Sesama community reap the results of social capital management that is increasing the number of worshipers and members in the Jaga Sesama community, strong values of brotherhood and kinship, and the creation of business relationships. The Jaga Sesama community still needs to develop a social network that bridges the outside (bridging) in order to create a wider relationship.